PENINGKATAN KETERAMPILAN MENULIS DESKRIPSI DENGAN PENDEKATAN KONSTRUKTIVISME DI KELAS IV SDN 29 GADIH ANGIK - Fitri, Yulia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based on observation of fourth grade of SDN 29 Gadih Angik Tanjung Mutiara,  students achievement in lesson of skilled of writen is still low. It was done by class action research. The goal of this study was to describe the planning, implementation, and learning outcomes. Data collected by using a qualitative and quantitative approach. Learning strategy used by contruktivisme approach. After doing the research the student learning Civic improved. It can be seen, both from teachers ability in designing learning increased from 78,1% up to 93%, teacher activity increased from 75 % to 93%, student activity increased from 87% to 96%. In sum, the result of students learning increased 73,9 to 84,03 Kata kunci: keterampilan menulis, pendekatan konstruktivisme, SD